Saber ver a paisagem: aportes para a leitura de sítios protegidos e suas áreas de entorno - Isabela Cristina de Assis Berg (2017)
This research deals with the existing relation between the ways of apprehending and interpreting sites of heritage value and the process of the landscape construction, which, in turn, assumes direct correspondence with the preservation of the tangible and intangible dimensions of cultural heritage and the constitution of the spirit of the places. It is justified by the fact that the contemporary context, characterized by new relations with temporal dimensions and by a scenario of acceleration, disorderly urban growth and a speculative real estate culture, which has no connection with local traditions, has negatively interfered in the context of ancient urban nuclei and in their landscapes. Considering the existence of lags in the methodologies of patrimonial assets and in the policies of planning and management of the territory that allows the occurrence of these damages, the objectives of this work, therefore, focus on searching contributions in authors of the heritage field - John Ruskin and Gustavo Giovannoni -, urban aesthetics - Camillo Sitte - and the landscape - Alain Roger, Arnold Berleant, Eugenio Turri and Rosario Assunto -, with the intention of proposing an approach to these nuclei from the recognition of its landscape dimension, considered more appropriate for allowing them to be taken in their relation with the territory and, therefore, subject to the influences of interventions carried out even outside the perimeters defined for their protection. Finally, it is presented as the main results obtained by the research, the verification of the pertinence of the intended approach and the recognition of the environmental conditions and the perception as essential factors to the preservation practice and management of patrimonial sites.